Effect of Maternal Influenza Vaccination on Hospitalization for Respiratory Infections in Newborns: A Retrospective Cohort Study - Regan, Annette; de Klerk, N.; Moore, H.; Omer, S.; Shellam, G.; Effler, P. (LIPPINCOTT WILLIAMS & WILKINS, 2016)
BACKGROUND: Infants are at increased risk of hospitalization for influenza. Although vaccinating women during pregnancy has been shown to reduce the incidence of influenza infection among newborns, population-based data are limited. METHODS: A population-based cohort of 31,028 mothers and singleton infants were included in the analysis. Hospitalizations with a principal diagnosis or additional diagnoses consistent with severe respiratory illness occurring during the 2012 and 2013 southern hemisphere influenza seasons were identified using a state-wide hospital discharge database. Newborns were defined as "maternally vaccinated" if the mother received influenza vaccine ≥14 days before delivery. Cox regression models were used to estimate adjusted hazard ratios for hospitalization. RESULTS: A total of 3169 infants were maternally vaccinated and 27,859 were unvaccinated; 732 hospitalizations were identified, 528 (69%) of which were for bronchiolitis. There were 21.9 hospitalizations per 100,000 person days among maternally vaccinated infants and 30.2 hospitalizations per 100,000 person days among unvaccinated infants. Maternally vaccinated infants were 25% less likely to be hospitalized for an acute respiratory illness during influenza season compared with unvaccinated infants (adjusted hazard ratio: 0.75, 95% confidence interval: 0.56-0.99, P = 0.04). Vaccinations administered in the third trimester were associated with a 33% reduction in the risk of newborn hospitalization (adjusted hazard ratio: 0.67, 95% confidence interval: 0.47-0.95, P = 0.03). No such reduction was identified for vaccinations administered earlier in pregnancy. CONCLUSIONS: Maternal influenza vaccination was associated with a reduction in the incidence of hospital admission for acute respiratory illness among infants <6 months of age. These data suggest that vaccination during third trimester may provide optimal benefit to the newborn.